Alteration and Exsolution Characteristics of Ilmenites of Moheskhali Island, Chittagong, Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2010)
Mineralogical analysis of Moheskhali beach sands revealed the presence of high amount of ilmenite. About 50% of these ilmenites are unaltered which are characterized by the presence of exsolution of ilmenite with hematite, ilmenite with magnetite, and ilmenite with rutile. Others (50%) are unexsolved where 30-50% grains partially or fully altered. These altered and unaltered phases of ilmenite are confirmed by X-Ray diffraction study. Ilmenite-hematite exsolution comprising 70-80% of the total exsolution. The widely banded exsolved phases were formed by continuous exsolution mechanism while the second generation thinner bands were formed discontinuously. Seriate texture dominates (about 75%) over emulsion, granular, quadrangular, sub graphic, veined and special types. Optical study suggests that the alteration of ilmenite is seen to proceed along grain boundaries and/or fractures resulting in an amorphous to microcrystalline mass resembling leucoxene. The chemical composition of the alteration products of ilmenite frequently fluctuates within definite ranges (pseudoilmenite and pseudorutile ranges) of a nonstoichiometric composition and thus deviates from their ideal composition. Key words: Ilmenite; Rutile; Opaque; Exsolution; Alteration. DOI: 10.3329/bjsir.v45i1.5173 Bangladesh J. Sci. Ind. Res. 45(1), 17-26, 2010